The impact of primary human papillomavirus screening on negative loop excision histology following biopsy‐proven high‐grade cervical intra‐epithelial lesions: A review from a large tertiary colposcopy unit. (10th September 2021) - Xie, Huan; Morton, Rhett; Balendran, Jananie; Philp, Shannon; Saidi, Samir; Farrell, Rhonda; Anderson, Lyndal; Pather, Selvan
Abstract : Background: The renewed National Cervical Screening Program incorporating primary human papillomavirus (HPV) screening was implemented in Australia in December 2017. In a previous study conducted in the UK, primary HPV screening was found to be associated with a 25% reduction in the incidence of negative histology following loop electrosurgery excision procedure (LEEP). Aim: To examine the change in incidence and associated risk factors for a negative LEEP with introduction of primary HPV screening. Materials and Methods: A retrospective review of the records of all patients undergoing a LEEP excision for biopsy‐proven high‐grade cervical intra‐epithelial lesions between 1 January 2014 and 30 June 2019 in a specialised centre. Results: There were 1123 patients who underwent a LEEP included in the analysis. The incidence of a negative LEEP specimen was 7.5% (59/784) and 5.3% (18/339) in the pre‐ and post‐HPV screening cohort. More patients in the post‐HPV screening group had low‐grade cytology on referral ( P  < 0.001), smaller cervical lesions on colposcopy ( P  = 0.012) and longer biopsy to treatment interval ( P  = 0.020). Primary HPV screening was associated with a significant reduction in the incidence of a negative LEEP specimen in a propensity matched cohort (11.2% to 5.1%, P  = 0.006) and a 41% ( P  = 0.045) decreased relative risk of a negative LEEP on multivariate analysis. Conclusions: Primary HPV screening results in a lower incidence of negative LEEP histology, despite a longer biopsy to treatment wait time and higher proportion of low‐grade cytology at triage.